EFEKTIFITAS PELAYANAN PUBLIK BANTO TRADE CENTRE ( BTC ) DI KOTA BUKITTINGGI - Mia Audinawati; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Trade center moving from traditional markets into a modern shopping center with a partnership with the tenants / buyers, to accommodate the needs of customers, and create a facility for the activities of shopping, entertainment, as well as the creation means stores representative as things that background development Banto Trade Center (BTC).The analytical method used is qualitative method. Data and information obtained through observation and interviews with snowballing technique. Based on the effectiveness of the public servants known that his lack of public interest in BTC dikarenan some things that a stall condition, the parking lot, the existing facilities in the BTC and the lack of promotion by the BTC.All of these conditions according to traders which also cause people are not interested to visit and shop in BTC so that the low trade transactions and trade turnover will not be achieved in accordance with what they expect.To conclude, this research finds that because of those problems, then people prefer other locations as a place to trade. Based on the need for the seriousness of the manager in increasing public interest in the BTC and the need for improvements to BTC in terms of physical and BTC program and increased promotion by the manager.Keywords: Banto Trade Centre, Public Service Effectiveness